Advanced Writing Courses through Online Learning: Thai EFL Learners’ Perception - Kirana, Satwika Nindya; Gupta, Yash Munnalal (English Education Department, Universitas Islam Indonesia, 2023)
The study aims at analyzing Thai students’ perception as EFL learners on advanced writing courses taught and learned online. The participants are 100 Nakhon Sawan Rajabhat University students in Year 3 and 4 majoring in English, English Education, and English for Business Communication. The participants have experienced online writing courses in Research Report Writing, Essay Writing, Creative Writing, and Business Writing subject. The data were collected using a survey and an in-depth interview to 20 of the participants. The results show that the challenges that the students face in learning advanced writing courses online outweigh the advantages. The students’ main problem were the difficulty in comprehending the lessons and the teachers’ explanations as well as the feedback. The second challenge were the poor internet connection. They are problems due to the lack of skills and technical devices. The other problem was due to the more workload in having an online advanced writing courses. And finally the last problem is that online classes make the learners feel alienated, disengaged, and demotivated. Besides the problems faced, the learners admitted that learning advanced writing online provides more flexible time in constructing the pieces of writing and they feel less pressured in writing since the teachers do not supervise them in person.